Trading behaviors on knowledge of price discovery in futures markets - Qingbin Gong; Zili Tang; Bing Xu (Journal of Innovation & Knowledge (JIK), 2021)
The financial market provides a mechanism for aggregating information of heterogeneous traders, who have different beliefs, knowledge and trading strategies. This paper studies the interactions between heterogeneous traders and their impacts on price discovery by developing a pricing model for the futures market. With mathematical analysis, we solve the equilibrium and its stability conditions for the system. As the findings show, behavioral factors such as risk appetites, degree of rationality and market liquidity have a combined effect on stability conditions. When the stability conditions are satisfied, the market can aggregate the information to form 'good knowledge' about the price. If investors have high risk appetites or a high degree of rationality, it is difficult for the market to realize the price discovery function.
Keywords: 650; Decision-making; Knowledge; Bounded rationality; Heterogeneous agents; Price discovery